Urban Redevelopment Policies on the Move: Rethinking the Geographies of Comparison, Exchange and Learning. (25th March 2018) - Ward, Kevin
Abstract: Recent years have seen the emergence of two interrelated strands of work in the field of English‐speaking urban studies. The first has centred on rethinking notions of place along relational lines. The second centres on rethinking what an attention to the city in the world might mean for understanding the arriving at and making up of urban policy. Taking its cue from the intersection of these two strands, this article explores the forging of Edinburgh's tax increment financing (TIF) policy. It highlights how those in the city drew upon experiences from elsewhere (both relatively close to home and further afield) in assembling the policy and the particular 'local' politics over its translation/adoption/failed introduction. The article argues for an approach to urban policy mobility studies which is sensitive both to the ephemeral, indeterminate and open‐ended ways in which policies are arrived at and made up, and the segmented and structured contexts that inform how policies appear and reappear in multiple locations.